Attenuation of widespread hypersensitivity to noxious mechanical stimuli by inhibition of GABAergic neurons of the right amygdala in a rat model of chronic back pain. (16th February 2022) - Tokunaga, Ryota; Takahashi, Yukari; Touj, Sara; Hotta, Harumi; Leblond, Hugues; Kato, Fusao; Piché, Mathieu
Abstract: Background: Chronic primary low back pain may be associated with hyperalgesia in uninjured tissues and with decreased pain inhibition. Previous studies have shown that the amygdala is involved in pain regulation and chronic pain, that neuronal activity in the amygdala is altered in models of persistent pain, and that the central nucleus of the right amygdala plays an active role in widespread hypersensitivity to noxious stimuli. Methods: Behavioral, electrophysiological, biochemical, and chemogenetic methods were used to examine the role of the central nucleus of the right amygdala in hypersensitivity to noxious stimuli in a rat model of chronic back pain induced by a local injection of Complete Freund Adjuvant (CFA) in paraspinal muscles. Results: CFA produced chronic inflammation limited to the injected area. CFA‐treated rats showed increased pain‐like (liking) behaviors during the formalin test compared with controls. They also showed widespread mechanical hypersensitivity compared with controls, which persisted for 2 months. This widespread hypersensitivity was accompanied by altered activity of different types of right amygdala neurons, as shown by extracellular recordings. Plasmatic levels of IL‐1β, IL‐6, and TNF‐α were not elevated after 1 or 2 months, indicating that persistent widespread hypersensitivity is not caused by persistent systemic inflammation. However, chemogenetic inhibition of GABAergic neurons in the right amygdala attenuated widespread mechanical hypersensitivity. Conclusions: These findings indicate that chronic widespread mechanical hypersensitivity in a model of chronic back pain can be attenuated by inhibiting GABAergic neurons of the right amygdala, and that widespread hypersensitivity is not maintained by chronic systemic inflammation. Significance: The amygdala is a key structure involved in pain perception and modulation. The present results indicate that the GABAergic neurons of its central nucleus are involved in widespread hypersensitivity to noxious stimuli in a rat model of chronic back pain. The inhibition of amygdala GABAergic neurons may be a potential target for future interventions in patients with chronic back pain.